Ginger (Zingiber Officinale) and Mint Leaves (Mentha Piperrita L) Alleviate Emesis Gravidarum - Indah Putri Ramadhanti; Uli Hermalina Lubis (Women, Midwives and Midwifery, 2021)
Background: Emesis gravidarum is a feeling of nausea that appears in pregnant women, especially in the morning. Pregnant women experience nausea, vomiting, 2% in the morning, 80% throughout the day and 18% progress to delivery. In Indonesia, there are 50-75% cases of nausea and vomiting experienced by pregnant women. The cause is an increase in the hormones estrogen, progesterone and the secretion of hCG. The content in ginger (Zingiber OffIcinale) and mint leaves (Mentha Piperrita L) can reduce the incidence of emesis gravidarum thereby preventing bad health conditions of pregnant women that interfere with fetal growth and development. Purpose: To know the effectiveness of giving ginger and mint leaves to reduce emesis gravidarum for pregnant women. Methods: The research method used is the Quasy Experiment method with the Two Group Pre and Post-Test Design approach. The population of first trimester pregnant women is 60 people. The number of samples in each group was 4 women using the 2 free sample formula and purposive sampling technique. The results of the normal distribution test with the Saphiro Wilk test, the data are normally distributed so that it uses the paired t-test and the independent t-test. Results: Based on the univariate test, it was found that the average before infusion of ginger was 9.25 and 5.25 after being given steeped ginger. On average, before being given the mint leaf steeped was 10.0 and after being given the mint leaf steeped was 7.00. Based on the paired t-test, it was found that the p-value of steeped ginger was 0.011 <0.05, while the p-value of steeped mint leaves was 0.024 <0.05. Based on the independent t-test, it was found that the effectiveness of giving steeped ginger and mint leaves was p-value 0.013 <0.05. Conclusion: Ginger and mint leaves statistically alleviate emesis gravidarum in the first trimester of pregnancy. Midwives could suggest the women to consume ginger and mint leaves as alternative or complementary treatment of emesis gravidarum.